Transcriptomic studies of systemic lupus erythematosus - Masahiro Nakano; Yukiko Iwasaki; Keishi Fujio (BMC, 2021)
Abstract The management of systemic lupus erythematosus (SLE) remains challenging for clinicians because of the clinical heterogeneity of this disease. In attempts to identify useful biomarkers for the diagnosis of and treatment strategies for SLE, previous microarray and RNA sequencing studies have demonstrated several disease-relevant signatures in SLE. Of these, the interferon (IFN) signature is complex, involving IFNβ- and IFNγ-response genes in addition to IFNα-response genes. Some studies revealed that myeloid lineage/neutrophil and plasma cell signatures as well as the IFN signature were correlated with disease activity, lupus nephritis, and complications of pregnancy, although some of these findings remain controversial. Cell-type-specific gene expression analysis revealed the importance of an exhaustion signature in CD8+ T cells for SLE outcome. Recent single-cell RNA sequencing analyses of SLE blood and tissues demonstrated molecular heterogeneity and identified several distinct subpopulations as key players in SLE pathogenesis. Further studies are required to identify novel treatment targets and determine precise patient stratification in SLE. In this review, we discuss the findings and limitations of SLE transcriptomic studies.